DNA-based method for identification of species origin of honey and edible bird’s nest - Chin, Nyuk Ling; Kek, Siok Peng; Quek, Meei Chien (2016)
Food traceability is increasingly important and identification of food source and its origin will give both consumers and industry players a better sense of security. The species origins of honey and edible bird's nest were identified using DNA-based method through procedures of DNA extraction, polymerase chain reaction (PCR) amplification and DNA sequencing, and finally construction of phylogenetic tree. The results showed that honeys and edible bird's nests were successfully clustered to their bee and swiftlet species origins, respectively. This approach suggests that DNA-based method is used as an identification method for food such as honey and edible bird's nest.